Volunteer engagement and intention to quit from a self‐determination theory perspective. Issue 9 (21st August 2013) - Haivas, Simona; Hofmans, Joeri; Pepermans, Roland
Abstract: Drawing on self‐determination theory, the current study investigates the mediation process of satisfaction with the 3 basic needs (i.e., autonomy, competence, relatedness) between autonomous motivation and volunteers' turnover intention and work engagement. A study of 349 Romanian volunteers reveals an interesting dichotomy. For work engagement, the positive effect of autonomy and competence needs satisfaction appears to have been partially mediated by autonomous motivation. Turnover intention, however, was directly influenced by the degree of autonomy and competence needs satisfaction. Moreover, satisfaction of the relatedness need had no effect on the 2 outcome variables when controlling for satisfaction of autonomy and competence needs. Implications and possible explanations are suggested.